Removal of As(III) and As(V) from water using green, silica-based ceramic hollow fibre membranes via direct contact membrane distillation - Hubadillah, Siti Khadijah; Othman, Mohd Hafiz Dzarfan; Sheikh Abdul Kadir, Siti Hamimah; Jamalludin, Mohd Riduan; Harun, Zawati; Abd Aziz, Mohd Haiqal; A. Rahman, Mukhlis; Jaafar, Juhana; Mikihiro, Nomura; Sawao, Honda; Iwamoto, Yuji; Fansuri, Hamzah (Royal Society of Chemistry, 2019)
Arsenite [As(III)] and arsenate [As(V)] removal by direct contact membrane distillation (DCMD) using novel hydrophobic green, silica-based ceramic hollow fibre membranes derived from agricultural rice husk was investigated in this work. The green ceramic hollow fibre membranes were prepared from amorphous (ASHFM) and crystalline (CSHFM) silica-based rice husk ash and modified to be hydrophobic via immersion fluoroalkylsilane (FAS) grafting of 1H,1H,2H,2H-perfluorodecyltriethoxysilane. Superhydrophobic contact angle values up to 157° and 161° were obtained for ASHFM and CSHFM, respectively. Remarkably, the membrane surface morphology mimicked a look-alike lotus-leaf structure with decrement in pore size after grafting via the silane agent for both membranes. The effect of arsenic pH (3–11), arsenic concentration (1–1000 ppm) and feed temperature (50–80 °C) were studied and it was found that feed temperature had a significant effect on the permeate flux. The hydrophobic CSHFM, with a flux of 50.4 kg m−2 h−1 for As(III) and 51.3 kg m−2 h−1 for As(V), was found to be the best of the tested membranes. In fact, this membrane can reject arsenic to the maximum contaminant level (MCL) limit of 10 ppb under any conditions, and no swelling mechanism of the membranes was observed after testing for 4 hours.